Effects of low glucose microenvironment on the proliferation, migration and senescence of meniscus-derived stem cells - Jiabei, Tong; Alzahrani, Badr; Subbiah, Suresh Kumar; Rampal, Sanjiv; Ramasamy, Rajesh; Zhijie, Ma; Xiaoyun, Wu; Pooi, Ling Mok (Nature Research, 2025)
Meniscus-derived stem cells (MeSCs) hold great promise for cytotherapy of the meniscus. Large-scale cell expansion in vitro is usually accompanied by decreased proliferation and migration and increased senescence, leading to a decrease in treatment efficiency. Therefore, the present study aimed to compare the effects of different concentrations of glucose on the proliferation, migration, senescence and protein expression of MeSCs. In this study, human MeSCs were cultured in two types of expansion media: low-glucose (LG) DMEM (5.5 mM glucose) and high-glucose (HG) DMEM (25 mM glucose). At specific passage number, the proliferation rate was evaluated by cell counting, the migration rate was evaluated by a scratch-wound assay, cell senescence was evaluated by β-GAL assays, and protein expression/phosphorylation was evaluated by ELISA. The results showed that a lower concentration of glucose promoted proliferation and migration, reduced cell senescence, and activated PI3K/Akt-related signaling pathways. This study provides a preliminary basis for the use of this medium composition for MeSC expansion.